Report of the Working Group on Development and Welfare of Scheduled Castes During Eighth Five-Year Plan - Ministry of Welfare, Government of India (Ministry of Welfare, Government of India, 1990)
The report of the Working Group on Development and Welfare of Scheduled Castes during the Eighth Five-Year Plan presents a comprehensive review of the socio-economic conditions, development strategies, and policy interventions aimed at uplifting Scheduled Castes in India. It highlights that Scheduled Castes, constituting a significant proportion of the population, are predominantly rural, economically disadvantaged, and socially marginalized, with a large share engaged in low-income agricultural labour and traditional occupations. Despite constitutional safeguards and multiple development initiatives, including the Special Component Plan, Special Central Assistance, and Scheduled Castes Development Corporations, progress has been uneven due to persistent issues such as poverty, low literacy rates, especially among women, inadequate access to education, and continued social discrimination including remnants of untouchability. The report underscores that educational deprivation, lack of viable economic opportunities, and insufficient asset ownership reinforce the cycle of poverty. While financial allocations and coverage targets during the Sixth and Seventh Plans showed quantitative improvement, qualitative deficiencies in implementation—such as poor targeting, weak administrative coordination, inadequate monitoring, and non-viable schemes—limited the overall impact. It emphasizes the need for enhanced resource allocation proportional to population share, improved institutional mechanisms, stronger monitoring systems, and targeted interventions to ensure effective delivery of benefits. The report ultimately advocates for a more integrated, focused, and equity-driven strategy to enable Scheduled Castes to achieve socio-economic parity and sustainable development.
Government of India, Ministry of Welfare
Ministry of Welfare, Government of India
Keywords: Scheduled Castes Development, Eighth Five-Year Plan, Rural Population, Poverty and Inequality, Agricultural Labourers, Special Component Plan, Educational Backwardness, Social Discrimination, Economic Empowerment, Scheduled Castes Development Corporations, Central Assistance Schemes, Implementation Deficiencies